OPTIMIZING PHYSIOTHERAPY MANAGEMENT FOR UPPER EXTREMITY MOTOR RECOVERY IN POST-STROKE PATIENTS: A LITERATURE REVIEW OF CURRENT APPROACHES - Widanti, Herista Novia; Arti, Widi (JURNAL PROFESIONAL FISIOTERAPI, 2025)
Introduction: Stroke is an acute neurological disorder that can lead to significant motor deficits, particularly in the upper extremities, impacting daily activities and patients' quality of life. Physiotherapy rehabilitation programs plays a critical role in restoring motor function in stroke patients. Objective: This study aims to summarize secondary data regarding various physiotherapy interventions for upper extremity rehabilitation in stroke patients. Methods: A literature review method was employed, analyzing articles from academic databases such as PubMed, Google Scholar, and ScienceDirect. Inclusion criteria included articles published within the last five years (2020-2024), in English, and randomized controlled trials. Results: From seven analyzed articles, interventions like neuromuscular electrical stimulation (NMES) combined with robotics, task-oriented training, and virtual reality therapy demonstrated effectiveness in improving upper extremity motor functions in stroke patients. Conclusion: Technology-based physiotherapy interventions, especially the combination of NMES and robotics, along with task-oriented approaches, are effective in upper extremity motor recovery for stroke patients. Evidence-based practice in physiotherapy rehabilitation strategies are essential to ensure more inclusive and effective therapy. Keywords: Post-Stroke, Upper Extremity, Motor Recovery, Physiotherapy Intervention, Stroke Patient